Temporal and spatial heterogeneity of host response to SARS-CoV-2 pulmonary infection - Niyati Desai (Nature Portfolio, 2020)
Understanding the pathology in the lungs of patients with COVID-19 might provide clues as to the susceptibility of patients and how the SARS-CoV-2 virus can be fatal. Here the authors analyze cadaveric pulmonary tissue and show one group with high viral load, early death, inflammation and inflammatory damage, and another with low viral load, longer duration of disease, and more M2-like polarization and fibrotic lung damage.